Hujjiyah Nazariyah Saddiaz-Żarāiʻfī al-Fiqh al- Islāmywatatbīquhāfī Qadāyāal-Maʹkȗlātwa al- Mashrȗbātwa al-Malbȗsāt - Imam Sujoko (Insaniyat : Journal of Islam and Humanities, 2017)
This  study  entitled:HujjiyahNazariyahSaddiaz-Żarāiʻfī  al-Fiqh  al-IslāmywatatbīquhāfīQadāyāal-  Maʹkȗlātwa  al-Mashrȗbātwa  al-Malbȗsāt,  deal  with  the  theory  ofSaddiaz-Żarāi.  The  study  tries  to  explore  its  meaning,  concept,  and  its  legality  in  Islamic  jurisprudence,  and  how  it  could  be  implemented in the cases of food, drink and clothing. Food, drink and clothing are the primary need  of  human,  but  there  are  some  cases  faced  by  Muslim  related  to  the  food,  drink  and  clothing.  For  example a Muslim will consume a product of food or drink or clothingthat produced from the non  Muslim country which they do not mind about the material; halal or haram. Should Muslim stops  from using those product, based on the theory of Saddiaz-Żarāiʻ?. The study found that the theory of  Saddiaz-Żarāiʻ,is a one of the Islamic resources regarding to the majority of Muslim scholar, event  there  are  some  differences  among  them  related  to  its  implementation.  And  some  Muslim  scholar  does  not  recognize  Saddiaz-Żarāiʻ  as  Islamic  resources.  But  for  those  who  agree  with  the  theory  ofSaddiaz-Żarāiʻ,they should understand the regulation of Saddiaz-Żarāiʻ. The methodology of study  is library study which is referring to the Islamic references such as texts of Qur’an and hadis and its  exegesis, Islamic jurisprudence books both classic and modern book, and fatwa of modern Muslim scholarsDOI: 10.15408/insaniyat.v2i1.6591